Correction: MicroRNAs Expression in the Ileal Pouch of Patients with Ulcerative Colitis Is Robustly Up-Regulated and Correlates with Disease Phenotypes. - Shay Ben-Shachar; Henit Yanai; Hadas Sherman Horev; Hofit Elad; Liran Baram; Ofer Isakov; Hagit Tulchinsky; Metsada Pasmanik-Chor; Noam Shomron; Iris Dotan (PLoS ONE, 2016)
[This corrects the article DOI: 10.1371/journal.pone.0159956.].